A comparative analysis of authorized and unauthorized compound terms taken from the Library of Congress subject headings in information retrieval - Bernabe, Mary Jean Z. (2001)
This study is a comparative analysis of the authorized and unauthorized terms taken from the Library of Congress Subject Headings. It focused in which of the paired terms-authorized / LCSH or unauthorized/non-LCSH would give better recall and precision.